Eating competence and aspects related to a gluten-free diet in Brazilian adults with gluten-related disorders - Oliveira, Pâmela Mayara de (2022)
This cross-sectional study aims to assess eating competence (EC—an intra-individual approach to food, behaviors, and attitudes related to food) and aspects related to a gluten-free diet (GFD) in Brazilian adults with gluten-related disorders (GRDs). The research was conducted using an online survey with a self-reported instrument consisting of 40 items, organized into three parts: (I) Socioeconomic and demographic data; (II) the Brazilian version of the Eating Competence Satter Inventory (ec-SI2.0™BR); and (III) questions about adherence and difficulties in following the gluten-free diet. EC was measured by the ecSI2.0™BR instrument, with scores >= 32 were considered competent eaters. The instrument was applied nationwide through the GoogleForms® platform from 14 February 2022 to 30 March 2022. The publicity for the recruitment was supported by Brazilian celiac local and national associations (Acelbras and Fenacelbra), pages of food services or personal pages of tips and posts about gluten-related disorders, and specialized stores that offer gluten-free foods. The recruitment occurred through social networks (emails, Facebook groups, WhatsApp, and Instagram). A total of 1030 Brazilians with GRDs answered the questionnaire. Most participants were female, aged 40 years or older, with an income >R$3000, and a high education level. The main difficulty regarding adherence to GFD was the high cost of gluten-free foods. Individuals younger than 40 years old had lower EC scores, with no differences between men and women. Increasing socioeconomic status, schooling, and culinary practices increased the total score. Participants who “never/almost never” felt socially judged because their diet had higher scores for total EC. Competent eaters GRD individuals (EC >= 32) were mostly individuals aged >= 40 y/o; with income > R$3000; following a GFD; satisfied with purchased gluten-free products; consuming gluten-free products prepared at home, mainly by themselves; who do not feel judged because of the GRD and who feel that they can live a normal life with GRD. Our study showed that individuals who strictly adhere to the GFD have higher scores on eating competence than those who sometimes follow the treatment.